2021
DOI: 10.3390/jcm10184153
|View full text |Cite
|
Sign up to set email alerts
|

Initial Pro Re Nata Brolucizumab for Exudative AMD: The PROBE Study

Abstract: The present study aimed to determine the efficacy and safety of pro re nata (PRN) intravitreal brolucizumab therapy for neovascular age-related macular degeneration (AMD) without a loading dose in the real-world setting. The PROBE study (Pro Re Nata Brolucizumab for Exudative AMD) is a retrospective, observational, multicentric study that included 27 treatment-naïve patients (27 eyes) with neovascular AMD who received PRN brolucizumab therapy with the treatment interval being at least 8 weeks, should the need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 27 publications
1
26
2
Order By: Relevance
“…The first real-world studies of brolucizumab for AMD seem to confirm these data [18,19], both in treatment-naïve eyes and when switching from another therapy [18,20]. However, the increased, although still rare, the occurrence of intraocular inflammatory adverse events (which can lead to vascular occlusion and vision loss) for this new molecule means a change in the treatment paradigm toward injections that are more spaced out is likely, helped by its improved efficacy [21]. In the coming years, the therapeutic arsenal will be totally transformed by numerous molecules in development [22], and the discovery of new therapeutic targets [23], with the aim of reducing the therapeutic burden and improving visual outcomes.…”
mentioning
confidence: 90%
“…The first real-world studies of brolucizumab for AMD seem to confirm these data [18,19], both in treatment-naïve eyes and when switching from another therapy [18,20]. However, the increased, although still rare, the occurrence of intraocular inflammatory adverse events (which can lead to vascular occlusion and vision loss) for this new molecule means a change in the treatment paradigm toward injections that are more spaced out is likely, helped by its improved efficacy [21]. In the coming years, the therapeutic arsenal will be totally transformed by numerous molecules in development [22], and the discovery of new therapeutic targets [23], with the aim of reducing the therapeutic burden and improving visual outcomes.…”
mentioning
confidence: 90%
“…Results revealed significant mean BCVA increase, CST reduction and fluid resolution in approximately 75% of eyes after two injections. 63 The same research team suggested that intravitreal brolucizumab may be beneficial for nAMD patients who develop an RPE tear, either as primary or switch therapy. 64 …”
Section: Real-world Clinical Datamentioning
confidence: 99%
“… Bilgic et al, The PROBE Study. 63 2021 Retrospective, observational, multicentre 27 (27) 1. Mean BCVA showed notable improvement from 57.4 ± 4.5 ETDRS letters at baseline to 65.3 ± 3.12 letters at the final examination (p = 0.014).…”
Section: Real-world Clinical Datamentioning
confidence: 99%
See 2 more Smart Citations